Pengaruh Latihan Small Side Games Terhadap Kemampuan Passing Dan Endurance Pada Tim Futsal Sheyfa Academy (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the effect of small side games training on passing and endurance abilities in the futsal sheyfa academy. This research is a quantitative research with an experimental approach. The population and sample of this study were 20 Sheyfa Academy players. The data collection technique was carried out by means of tests and measurements. Data analysis using t test. Based on the results of the t test it can be seen that tcount 6,249 and ttable 2,110 with a significance value of 0,000. Because t count 8.304> t table 2.110, and the significance value is 0.000 <0.05, the results show that there is a significant difference. Research conclusions, based on the results of data analysis, descriptions, examination of research results, and discussion. It can be concluded that there is a significant effect of small side game training media on passing abilities and endurance abilities. Researchers suggest to coaches that small side games can be used as an alternative exercise to improve players' passing and endurance abilities.